WAYS OF DEVELOPING SCHOOL LEARNERS’ ENGLISH LANGUAGE COMPETENCIES THROUGH SMART TECHNOLOGIES (A CASE OF SECONDARY SCHOOLS IN CHIMBAY DISTRICT) - Nurniyazov Nursultan Jalgasovich (International Journal of Literature and Language Studies, 2026)
Aim — to examine the relationship between access to digital technologies and the development of English language competencies among students in secondary schools in Chimbay District, and to determine the effectiveness of smart technologies in the educational process. Methods — a three-stage pedagogical experiment was conducted, consisting of a diagnostic pretest, a formative intervention, and a control posttest. The study involved 60 learners, including 30 in the experimental group and 30 in the control group. The internal reliability of the measurement instrument was confirmed by Cronbach’s α = 0.87. Group differences were assessed using a t-test, while the effect size was evaluated using Cohen’s d. The frequency of smart technology use averaged 2.7 sessions per week (SD = 0.95). Results — in the experimental group, the mean English language competency score increased from 43 points (SD = 2.88) in the pretest to 58.27 points (SD = 2.57) in the posttest, representing a mean gain of 15.27 points. In comparison, the control group demonstrated a gain of 5.1 points. Following the intervention, positive changes were observed in learners’ motivation and engagement in the learning process. The post-intervention results showed 24 learners at a high level, 28 at a medium level, and 8 at a low level. The difference between the experimental and control groups was statistically significant (p = 0.03). Conclusion — the effective integration of smart technologies has a positive impact on the development of English language competencies. The findings suggest that active learner participation, regular feedback, and well-designed pedagogical interventions are more important for achieving positive learning outcomes than the frequency of technology use alone. This approach can provide a methodological basis for competence-oriented lesson design and systematic monitoring of learner progress in English language education.